LED driver IC design - Tan, Chee Kim (Nanyang Technological University, 2023)
In the modern world, the solution for automotive lighting seeks for a quality improvement such as the reliability, ease of usage and the safety of the users. The optimal solution is to design a constant current source that is capable to program both analog and digital dimming. In this project, the author was tasked to design a strings of LED diodes. This can be achieved by designing a three to eight channels programmable current source driver using BCD technology. With the aid of Pulse Width Modulation (PWM) duty cycle control, a programmable resistor and digital diming can provide analog current setting. An extensive diagnostics and fault recovery logic will be integrated to detect various short and open conditions of the LED, global and individual fault handling, respectively. In addition, to prevent overheating, a temperature sensing and thermal foldback such that the device will self-regulate its output current will also be implemented. Once the temperature exceeds its limit, the device will automatically activate a shutdown with hysteresis for recovery.